Prognostic Value of Braden Scale in Patients With Acute Myocardial Infarction: From the Retrospective Multicenter Study for Early Evaluation of Acute Chest Pain. Issue 6 (November 2020) - Jia, Yu; Li, Hong; Li, Dongze; Li, Fanghui; Li, Qin; Jiang, Ying; Gao, Yongli; Wan, Zhi; Cao, Yu; Zeng, Zhi; Zeng, Rui
Abstract : Background: The Braden Scale (BS) is a routine nursing measure used to predict pressure ulcer events; it is recommended as a frailty identification instrument. Objective: We aimed to evaluate the predictive utility of the BS in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention. Methods: We enrolled 2285 patients with AMI from the Retrospective Multicenter Study for Early Evaluation of Acute Chest Pain. The patients were divided into 3 groups (B1, B2, and B3) according to their BS score (⩽12 vs 13–14 vs ≥15). The primary endpoint was all-cause death. Results: There were 264 (12.0%) all-cause deaths during the median follow-up period of 10.5 (7.9–14.2) months. In-hospital and midterm mortality and other adverse outcomes increased with decreases in the BS score. The Kaplan-Meier survival analysis showed that patients with a lower BS score had a lower cumulative survival rate ( P < .001). The multivariate Cox regression analysis showed that a decreased BS score was an independent predictor for all-cause mortality (B2 vs B1: hazard ratio, 0.610; 95% confidence interval, 0.440–0.846; P = .003; B3 vs B1: hazard ratio, 0.345; 95% confidence interval, 0.241–0.493; P < .001). Conclusions: The BS at admission may be a useful routine nursing measure to evaluate the prognosis of patients with AMI. The BS may be used to stratify risk at early stages and to identify those who may benefit from further assessment and intervention due to frailty syndrome. Abstract : Supplemental digital content is available in the text.